Fast versus turbulent fluidization of Geldart Group B particles - Chew, Jia Wei (2021)
Both fast and turbulent fluidized beds exhibit entrainment, but the differences in the flow phenomena are not well understood. This study targeted a comparative analysis of the cluster (or streamer), mass flux, and segregation datasets from these two fluidization regimes. The particle systems were narrow particle size distributions (PSDs), binary mixtures, or broad PSDs of Geldart Group B particles. Relative to the fast fluidized bed, the turbulent bed exhibited (i) higher cluster probability and frequency, but lower cluster duration; (ii) lower local mass flux; and (iii) similar segregation extents. Regarding clusters, the relative dominance of the variables on probability was similar for both regimes, but there was a difference for probability and frequency. For overall mass flux, particle-related properties were more dominant with the turbulent bed. As for segregation, the radial position was the most influential in the fast fluidized bed, but the least in the turbulent one.